Prediktor Intensi Merokok pada Remaja di Kota Banda Aceh - Meutuah, Rizkina; Afriani; Faradina, Syarifah; Amna, Zaujatul (INSAN Jurnal Psikologi dan Kesehatan Mental, 2023)
One of the problems experienced by adolescents is excessive smoking behavior, which can trigger negative physical and psychological impacts. Smoking intention is one of the antecedents of smoking behavior. Social factors (e.g., parental monitoring and peer pressure) and broader environmental factors (e.g., media exposure) can predict adolescent smoking intention. The objective of this study is to determine the predictors that contribute significantly between parental monitoring, peer pressure, and media exposure to smoking intentions in adolescents. This study involved 161 teenage boys and girls in Banda Aceh. The results of multiple regression analysis indicate that significant predictors of smoking intention are peer pressure and parental control which is a subdimension of parental monitoring. The implication of this study is the importance of having a positive peer environment and parental monitoring as protective factors from the risk of adolescent smoking behavior.